2006
DOI: 10.1111/j.1439-0531.2006.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Fertility in Loosely Housed Sows and Gilts: Vulvar Discharge Syndrome, Environment and Acute‐phase Proteins

Abstract: The effect of vulvar discharge syndrome (VDS) on sow and gilt fertility was studied on 26 farms. Of 824 animals inspected in 21 randomly selected and five VDS problem farms, 19 (2.3%) were afflicted with VDS. Altogether 542/799 of the examined animals (67.8%) farrowed thereafter. Nine of the 19 VDS animals (47.4%) and 533/780 non-VDS animals (68.3%) farrowed at the first chance after the examination (p = 0.05). None of the unmated gilts in this study had VDS. Environmental and individual factors likely to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
0
19
1
3
Order By: Relevance
“…2002; Sanders and Bilkei 2004). However, the results have not always been consistent, others have found no association between parity and VDS syndrome (Oravainen et al. 2006).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…2002; Sanders and Bilkei 2004). However, the results have not always been consistent, others have found no association between parity and VDS syndrome (Oravainen et al. 2006).…”
Section: Discussionmentioning
confidence: 74%
“…Some of these VDS cases could have been physiological. The first part of the study (Oravainen et al. 2006) showed that there was no systemic acute phase response connected with the syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations